HLA-DRB1 differences in allelic distribution between familial and sporadic multiple sclerosis in a Hellenic cohort. Issue 7 (3rd October 2019) - Katsavos, Serafeim; Artemiadis, Artemios; Gontika, Maria; Skarlis, Charalampos; Markoglou, Nikolaos; Davaki, Panagiota; Stamboulis, Eleftherios; Kilindireas, Konstantinos; Stefanis, Leonidas; Anagnostouli, Maria
ABSTRACT: Objective : Familial Multiple Sclerosis (fMS) is reported to have distinct clinical and imaging characteristics in comparison to the sporadic disease (sMS). Nevertheless, the genetic/immunogenetic profile of fMS has never been investigated in depth, so far. In this study, we examined differences of HLA-DRB1 allelic frequencies between 57 fMS and 141 sMS Hellenic patients, with reference to 246 previously genotyped healthy controls (HCs). Patients and Methods : All patients underwent medical interview and DRB1 genotyping, using a low-resolution SSOP technique. Statistical analyses were performed using SPSS v.21.0 software, with significance set at 0.05, and p value corrected according to the Benjamini–Yekutieli method. Results : 29 fMS cases had at least one 1 st degree relative affected (fMS 1 st ), while the rest had at least one 2 nd or 3 rd degree relative affected (fMS 2 nd /3 rd ). Parent-of-origin effects were observed, with the prevalence of maternal inheritance. Frequency of DRB1*15 was significantly increased in fMS and sMS, in comparison to HCs (p = 0.002 and <0.001, respectively). After fMS stratification, this result was mainly attributed to the fMS 2 nd /3 rd subgroup. DRB1*11 frequency was significantly decreased only in sMS (p < 0.001) with fMS approximating HCs' frequency, especially for the fMS 1 st subgroup. Heterozygosity was favored over homozygosity in all groups. Conclusion : We propose possible HLA-DRB1 allelic distribution differences between fMS and sMS, which become more apparent as proximity of affected relative/-es in fMS increases, supporting a rather degraded role of DRB1 alleles in fMS HLA/immunogenetics and indicating the concomitant implication of other HLA and non-HLA polymorphisms.